Shooting the talking head - Luft, Greg; First Light Video Publishing (Venice, CA. : First Light Video Publishing)
Explains regarding the shoorting process which is the photography and cinematography tecnique in producing and directiong film and motion pictures
Title from title screen
Keywords: Cinematography -- Technique; Photography -- Technique